The Role of Social Media Influencers in Brand Communication Strategy: Literature Review - Rizky Kertanegara (MEDIASI : Jurnal Kajian dan Terapan Media, Bahasa, Komunikasi, 2023)
Nowadays, influencers on social media are a trending and inevitable brand marketing tactic. Influencers, with their characteristics, can support the brand communication strategy activities. Companies or brand owners who use influencers in their advertising campaigns can influence sales volume, and increase brand recognition and consumer involvement in promotional activities. This article is a literature review regarding the influencer concept, its development, theoretical approaches, effectiveness models, to its role in brand communication strategy. To examine the role of using influencers on social media, several theories can be used, such as Social Learning Theory, Parasocial Theory, Attribute Theory, and Elaboration Likelihood Model Theory.